Severe asthma in children: therapeutic considerations. Issue 2 (April 2019) - Selby, Louise; Saglani, Sejal
Abstract : Purpose of review: Children with poor asthma control despite maximal maintenance therapy have problematic severe asthma (PSA). A step-wise approach including objective adherence monitoring and a detailed multidisciplinary team assessment to identify modifiable factors contributing to poor control is needed prior to considering therapy escalation. Pathophysiological phenotyping in those with true severe therapy-resistant asthma (STRA) and the current array of add-on therapies will be discussed. Recent findings: Adherence monitoring using electronic devices has shown that only 20–30% of children with PSA have STRA and need additional therapies. Omalizumab and mepolizumab are licensed for children with STRA aged 6 years and older. Although robust safety and efficacy data, with reduced exacerbations, are available for omalizumab, biomarkers predicting response to treatment are lacking. Paediatric safety data are available for mepolizumab, but efficacy data are unknown for those aged 6–11 years and minimal for those 12 years and older. A sub-group of children with STRA have neutrophilia, but the clinical significance and contribution to disease severity remains uncertain. Summary: Most children with PSA have steroid sensitive disease which improves with adherence to maintenance inhaled corticosteroids. Add-on therapies are only needed for the minority with STRA. Paediatric efficacy data of novel biologics and biomarkers that identify the optimal add-on for each child are lacking. If we are to progress toward individualized therapy for STRA, pragmatic clinical trials of biologics in accurately phenotyped children are needed.